Media Pengenalan Makanan Khas Daerah Sumatera Menggunakan Teknologi Augmented Reality Berbasis Android - Fitri Khairina Nst; Ilham Faisal; Kalvin Chiuloto (UIN Sumatera Utara, 2022)
The development of information and communication technology in the current globalization has been very rapid especially among the general public. One of them is augmented relity technology that is very developed as an application in the field of promotion and sales. Augmented relity itself is one of the technologies in object recognition in the field of multimedia. Augmented relity is a merger between two worlds, namely the virtual world into the real world, in other words objects in the virtual world we can display to the real world. The application of the concept of Augmented relity can increase the effectiveness and recognition of an object to be interesting. The recognition of an object by means of ordinary 2-dimensional images as a promotional medium, considered unattractive and does not utilize developing technology. In this case, the object introduced by Augmented relity technology is a typical food area of Sumatra, including North Sumatra, South Sumatra and West Sumatra. Because in this day and age the introduction of regional specialties is less known by the people of Indonesia. Therefore, researchers created